2016
DOI: 10.7863/ultra.15.12054
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Liver Stiffness Measured by Transient Elastography Predict Clinical Outcomes Among Patients With Chronic Hepatitis B

Abstract: Our findings suggest that transient elastography is an effective measurement tool for diagnosing and monitoring the histologic response in patients with chronic hepatitis B during antiviral treatment and can help avoid multiple liver biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(34 reference statements)
0
32
0
Order By: Relevance
“…Recently, several published studies evaluated the association of longitudinal LSM and clinical outcomes in patients with HBV . Li ZQ et aldemonstrated predictive factors of HCC in CHB patients with antiviral treatment, but only baseline LSM was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several published studies evaluated the association of longitudinal LSM and clinical outcomes in patients with HBV . Li ZQ et aldemonstrated predictive factors of HCC in CHB patients with antiviral treatment, but only baseline LSM was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Transient elastography with CAP is a Food and Drug Administration (FDA)-approved modality for the diagnosis and assessment of the severity of HS, which was performed using FibroScan® (Echosens, Paris, France) by experienced operators in this study (23). Results were considered valid only for transient elastography with at least ten successful shots, a successful rate of 60% or higher, and an interquartile median ratio of less than 30%.…”
Section: Cap Assessmentmentioning
confidence: 99%
“…34 In another study of patients with CHB, both the fibrosis index and ASTto-platelet ratio were shown to be able to predict substantial fibrosis. 35 Another study conducted by Zeng et al 36 found that FibroScan could predict the clinical outcome among patients with CHB. However, whether the AST-to-platelet ratio could predict a histologic response as effectively as FibroScan remained unknown.…”
Section: Discussionmentioning
confidence: 99%